A retrospective analysis of long-term outcomes following a single episode of transscleral cyclodiode laser treatment in patients with glaucoma. Issue 7 (6th July 2013) - Zhekov, Ivailo; Janjua, Razia; Shahid, Humma; Sarkies, Nicholas; Martin, Keith R; White, Andrew J R
Abstract : Objectives: To investigate the efficacy of a single cyclodiode laser photocoagulation treatment for refractory glaucoma and its effect on visual outcome in patients with good visual potential as well as to evaluate possible predictive factors in establishing optimal treatment parameters. Design: Retrospective observational study. Setting: Tertiary referral centre. Participants: The notes of 87 patients with refractory glaucoma who underwent cyclodiode photocoagulation as a first surgical intervention over a 7-year period. Main outcome measures: Maintenance of intraocular pressure (IOP) reduction, number of medications and visual acuity outcomes post-treatment. Results: The mean IOP after a single treatment decreased from 39.5±1.3 to 17.8±1.5 mm Hg after a 6-week follow-up period (p<0.0001). This reduction in IOP was maintained over a 3-year period. Here, 61.5% of patients were able to reduce the number of medications used, with mean reduction from 2.6 to 1.5 medications (p<0.05). The mean initial visual field loss prior to treatment was 8.74 dB and at 6 months post-treatment was measured at 9.06 dB (p>0.05), suggesting no significant overall change. Visual acuity remained unchanged or improved for 83.6% of patients (p>0.05) with relatively good visual potential (average vision preoperatively was 0.57 logMAR). Hypotony occurred in 5.3% of patients. No patients required enucleation or evisceration. Conclusions: A single session of cyclodiode laser therapy was associated with significant IOP reduction in a majority of patients with refractory glaucoma. The majority were able to maintain the IOP reduction over a 3-year period without the need for a further surgical intervention. Additionally, over 80% of the patients in our study were able to maintain their baseline visual acuity. These results support the view that a single cyclodiode treatment can be sufficient in achieving long-term IOP control and may be considered in eyes with relatively good visual potential.